The Yellow-green Bush-tanager is neither a bush-tanager nor a sparrow: Molecular phylogenetics reveals that Chlorospingus flavovirens is a tanager (Aves: Passeriformes; Thraupidae) - Avendaño, Jorge Enrique; Barker, F. Keith; Cadena, Carlos Daniel (Zootaxa, 2016)
Molecular phylogenetic analyses of the genus Chlorospingus (Aves: Emberizidae) indicate that the genus is not monophyletic because Chlorospingus flavovirens is actually a member of the tanager family (Thraupidae), in which its closest relatives are members of the genus Bangsia. We thus propose that C. flavovirens be transferred to Thraupidae and to the genus Bangsia.